2016
DOI: 10.1155/2016/2621383
|View full text |Cite
|
Sign up to set email alerts
|

Strangulated Morgagni’s Hernia: A Rare Diagnosis and Management

Abstract: Morgagni hernia is a rare type of congenital diaphragmatic hernia. It accounts for only 3% of all diaphragmatic hernias. The defect is small and hernia being asymptomatic in the majority presents late in adulthood. Obstruction or incarceration in Morgagni hernia is uncommon. We report a rare occurrence of strangulated Morgagni hernia. A 40-year-old gentleman presented to our emergency department with features of intestinal obstruction. Computed tomography of the chest and abdomen showed a strangulated right Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
(13 reference statements)
0
18
0
1
Order By: Relevance
“…7 In 90% of cases Morgagni hernias are seen on the right side while in 2% cases on the left side and almost 8% cases are bilateral. 7 It has been reported that almost 70 % cases of Morgagni hernias are females. 3 Although cases of Morgagni hernia can present in early childhood with respiratory symptomatology, most of the cases remain asymptomatic and are detected later in life.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…7 In 90% of cases Morgagni hernias are seen on the right side while in 2% cases on the left side and almost 8% cases are bilateral. 7 It has been reported that almost 70 % cases of Morgagni hernias are females. 3 Although cases of Morgagni hernia can present in early childhood with respiratory symptomatology, most of the cases remain asymptomatic and are detected later in life.…”
Section: Discussionmentioning
confidence: 96%
“…1 Morgagni hernias occur due to failure of fusion of the fibro-tendinous elements of diaphragm, that is, sternal and costal attachments, which leaves behind a muscle-free area known as the costosternal trigone or the space of Larrey or Morgagni's foramen through which the hernia occurs eventually. 7 Morgagni hernias are more common on the right side than the left due to extensive pericardial attachments on the left diaphragm. 7 In 90% of cases Morgagni hernias are seen on the right side while in 2% cases on the left side and almost 8% cases are bilateral.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of adults, women are more predisposed, as in our group. In adults, even the elderly, HM is incidentally discovered (81 asymptomatic cases published), imagistically or intraoperatively; or in the case of complications (2%) (intestinal or colon intestinal occlusion, gastric volvulus, large epiploon incarceration) (9,10). In 50% of cases, predisposing factors are encountered: obesity, multiparity, chronic obstructive pulmonary disease, constipation (11).…”
Section: Discussionmentioning
confidence: 99%